Pengaruh Polyurethan pada Kemampuan Meredam Suara Home Made Foam - Riki Perdana; Tri Utami; Devi Afriani; Erlin Eveline; Suparno Suparno (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2019)
Effective foam composition has been produced as sound absorbing material based on sound absorption coefficient value. The method used is experimentation, by mixing the main ingredients (polyurethan) with the developer liquid (isocyanate). There are five variations of research, with the isocyanate as a control variable. The results obtained from the first to fifth variations in a row are 0.152; 0.072; 0.042; 0.028 and 0.056. From the findings it can be concluded that the less polyurethan is added the greater the absorption coefficient value